The Semitic background of the New Testament - Fitzmyer, Joseph A. (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references and indexes.
" This combined edition reprints the text of two works, A wandering Aramean, originally published in 1979 by Scholars Pr, and Essays on the Semitic background of the New Testament, originally published in 1971 by Geoffrey Chapman Ltd"
Keywords: Dead Sea scrolls -- relation to the New Testament; Aramaic philology; Aramaic literature -- relation to the New Testament; Bible. N.T. -- language, style; Bible. N.T. -- Criticism, interpretation, etc